Tumor-initiating cells of breast and prostate origin show alterations in the expression of genes related to iron metabolism - Rychtarcikova, Zuzana; Lettlova, Sandra; Tomkova, Veronika; Korenkova, Vlasta; Langerova, Lucie; Simonova, Ekaterina; Zjablovskaja, Polina; Alberich-Jorda, Meritxell; Neuzil, Jiri; Truksa, Jaroslav (Oncotarget, 2017)
The importance of iron in the growth and progression of tumors has been widely documented. In this report, we show that tumor-initiating cells (TICs), represented by spheres derived from the MCF7 cell line, exhibit higher intracellular labile iron pool, mitochondrial iron accumulation and are more susceptible to iron chelation. TICs also show activation of the IRP/IRE system, leading to higher iron uptake and decrease in iron storage, suggesting that level of properly assembled cytosolic iron-sulfur clusters (FeS) is reduced. This finding is confirmed by lower enzymatic activity of aconitase and FeS cluster biogenesis enzymes, as well as lower levels of reduced glutathione, implying reduced FeS clusters synthesis/utilization in TICs. Importantly, we have identified specific gene signature related to iron metabolism consisting of genes regulating iron uptake, mitochondrial FeS cluster biogenesis and hypoxic response (ABCB10, ACO1, CYBRD1, EPAS1, GLRX5, HEPH, HFE, IREB2, QSOX1 and TFRC). Principal component analysis based on this signature is able to distinguish TICs from cancer cells in vitro and also Leukemia-initiating cells (LICs) from non-LICs in the mouse model of acute promyelocytic leukemia (APL). Majority of the described changes were also recapitulated in an alternative model represented by MCF7 cells resistant to tamoxifen (TAMR) that exhibit features of TICs. Our findings point to the critical importance of redox balance and iron metabolism-related genes and proteins in the context of cancer and TICs that could be potentially used for cancer diagnostics or therapy.
Keywords: regulace genové exprese u nádorů; Animals; myši transgenní; Drug Resistance, Neoplasm; Gene Expression Regulation, Enzymologic; biologický transport; nádory prsu; vztah mezi dávkou a účinkem léčiva; Female; Phenotype; regulace genové exprese enzymů; Mitochondria; tamoxifen; železo; Mice, Transgenic; ženské pohlaví; MFC-7 buňky; Gene Expression Regulation, Neoplastic; Leukemia, Promyelocytic, Acute; akutní promyelocytární leukemie; lidé; Antineoplastic Agents; Iron Chelating Agents; protinádorové látky; MCF-7 Cells; Breast Neoplasms; chemorezistence; nádory prostaty; stanovení celkové genové exprese; Prostatic Neoplasms; mitochondrie; Biological Transport; Dose-Response Relationship, Drug; Male; Iron; Neoplastic Stem Cells; Spheroids, Cellular; Principal Component Analysis; transkriptom; analýza hlavních komponent; fenotyp; zvířata; mužské pohlaví; Tamoxifen; Transcriptome; chelátory železa; buněčné sféroidy; Gene Expression Profiling; nádorové kmenové buňky; Humans